ANALYSIS OF INTRINSIC ELEMENTS IN SHORT STORIES BY WIDYA SUWARNA - Aisyah Putri Muhandra; Anniza Nursyahbani Siregar; Rizky Pratiwi; Hamidah Siloto; Diana Sopha (PHILOLOGY Journal of English Language and Literature, 2023)
This study aims to analyze the intrinsic elements in short stories by Widya Suwarna in terms of meaning and language. There are three titles of short stories analyzed namely“When the Sea is Angry”, “Calendar Mia Made”,and "The Beautiful Environment of Rini's Idea".The method used in this research is qualitative method. The results of this study found several intrinsic elements focused on Theme, Plot, Characters and Characterizations, Setting/Background, Point of View, Language Style and Message. On short stories"When the Sea is Angry"the theme of religion, in short stories“Mia's Custom Calendar”themed caring and on the story“The Beautiful Environment of Rini's Idea” environment themed. The three literary works of Widya Suwarna lead to stories with religious, caring and environmental themes which make a positive contribution to readers.